TRAINING FOR VILLAGE ECONOMIC EMPOWERMENT THROUGH COMMUNITY-BASED CONSUMPTION FISH AGRIBUSINESS DEVELOPMENT - Syifa, Fadilatus; Amelia Nurma Dewi, Lailatul; Zunaidi, Arif; Haris Khoironi, Ahmad (Proceedings of Annual Conference on Community Engagement, 2023)
This research aims to increase the economic empowerment of Joho Village through the "Community-Based Fish Agribusiness Development Training" program. Service methods include consumerist fish cultivation education and field practice involving the village head and village youth. Monitoring and evaluation results show significant improvements in fish growth and the effectiveness of cultivation techniques. This program has succeeded in empowering the community through the fish agribusiness sector, creating new opportunities, and improving economic prosperity in a sustainable manner. This research illustrates that a community-based approach can be an effective instrument for driving economic growth at the village level.